2013
DOI: 10.1111/trf.12455
|View full text |Cite
|
Sign up to set email alerts
|

The role of alloantibodies against human platelet antigen‐15 in multiply platelet transfused patients

Abstract: In this study, we found alloimmunization against HPA-15a and -15b in Japanese populations and demonstrated the relevance of these antibodies in a patient with PTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
19
2
Order By: Relevance
“…To the best of our knowledge, this study is the first to focus on multiple HPA-15 compatible and incompatible transfusions to explore the impact of HPA-15 alloantibodies on PTR. In contrast to our conclusion, Matsuhashi et al 12 demonstrated possible involvement of HPA-15b antibodies on PTR in one HPA-15-incompatible platelet transfusion. In their study, one more HPA-15 incompatible transfusion was performed, which resulted in a high CCI.…”
Section: Discussioncontrasting
confidence: 99%
“…To the best of our knowledge, this study is the first to focus on multiple HPA-15 compatible and incompatible transfusions to explore the impact of HPA-15 alloantibodies on PTR. In contrast to our conclusion, Matsuhashi et al 12 demonstrated possible involvement of HPA-15b antibodies on PTR in one HPA-15-incompatible platelet transfusion. In their study, one more HPA-15 incompatible transfusion was performed, which resulted in a high CCI.…”
Section: Discussioncontrasting
confidence: 99%
“…We conclude from our analysis that BBA can be considered a helpful initial screening tool in the PLT serology laboratory since analysis is fast and overall test specificity is very good. Major drawbacks of this method include 1) inadequate sensitivity for some specificities, which will require appropriate algorithms in the laboratory to avoid the release of false‐negative results, and 2) nonavailability of beads for the detection of HPA‐15 antibodies, which are relevant in causing FNAIT and PLT transfusion refractoriness, necessitating the use of additional testing.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnical variabilities of HPA frequency distribution As described above, the HPA systems involved in NAIT vary between Caucasian and Japanese, the HPA-1 system being predominant in the former and the HPA-4 system in the latter. As shown in Table 2 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], presently, there are reports on the frequency distribution of HPAs from different Asian countries, and although differences exist, it seems that the HPA-1 system, like in Japan, is not important in the majority of them. On the other hand, the HPA-4 system, which is important in Japan, is also relevant in South Korea and possibly Indonesia (2 contradictory reports), but not in the other countries.…”
Section: Treatmentmentioning
confidence: 99%